Anxiety is more related to inadequate eating habits in inactive than in physically active adults during COVID-19 quarantine - Christofaro, Diego G.D. [UNESP]; Tebar, William R. [UNESP]; Silva, Gabriela C.R. [UNESP]; Lofrano-Prado, Mara C.; Botero, Joao Paulo; Cucato, Gabriel G.; Malik, Neal; Hollands, Kristina; Correia, Marilia A.; Ritti-Dias, Raphael M.; Prado, Wagner L. (Elsevier, 2022)
Background & aims: Anxiety can be related to reduced diet quality during pandemics such as COVID-19. However, it is not clear whether these relationships would be similar in inactive and physically active participants. The aim of this study was to analyze associations between anxiety and eating habits in physically active and inactive individuals during the COVID-19 pandemic. Methods: The sample consisted of 1826 adults (58.5% women) who were invited through social media to answer an online questionnaire. The instrument included questions related to physical activity, eating habits, health behavior, mental health (anxiety, depression, self-esteem, sadness and stress) and overall health. Anxiety, food habits (high food habits consumption ≥5 times per week) and physical activity (≥150 min per week) were assessed during the COVID-19 pandemic. The relationship between anxiety and eating habits according to levels of physical activity (inactive vs. active) was assessed using binary logistic regression adjusted for sex, age, education level, social isolation, and body mass index. Results: Among the inactive participants, anxiety was related with high consumption of sweets (OR = 1.43; 95% CI = 1.11–1.83) and fast foods (OR = 2.23; 95% CI = 1.05–4.74) while quarantining during the COVID-19 pandemic. No relationship was observed between anxiety and food consumption among physically active participants in the final model. Conclusion: Anxiety was associated with less desirable eating habits among physically inactive adults during the COVID-19 pandemic.
Keywords: COVID-19; Eating habits; Exercise; Food; Mental health; Motor behavior